Pengaruh Daun Lembayung (Vigna sinensis L.) Terhadap Peningkatan Produksi Asi Pada Ibu Menyusui Bayi 0-6 Bulan - Eka Deviany Widyawaty; Dessy Hidayati Fajrin (2020)
Based on the Indonesian Demographic and Health Survey (IDHS), the coverage of infants who received exclusive breastfeeding in 2017 was 61.33%. One of the reasons mothers do not give breast milk is that the milk production is small and insufficient. Leaf of Lembayung (Vigna sinensis L.) is a plant that is well known to the public, easy to obtain and cheap. This lavender leaf is useful for stimulating the hormones oxytocin and prolactin such as alkaloids, saponins, polyphenols, steroids, and flavonoids. The purpose of this study was to see the effect of giving Lembayung leaves on the increase of milk production in breastfeeding mothers of infants aged 0-6 months in the Torjun Health Center, Sampang Regency. This research is a quantitative research with Quasi Experiment. Quasi-Experimental Research carried out two observations, observation of breast milk production before and after being given mauve leaves. The statistical test used was the Paired Sample T-Test with the results of the analysis of the value of p = 0.000